A comprehensive system for AASHTO PP69-10-based pavement rut evaluation using 1-mm 3D pavement surface model. Issue Volume 19:Issued 6(2018) (3rd June 2018) - Qiu, Shi; Wang, Kelvin C. P.; Zhang, Aonan; Li, Qiang Joshua; Moravec, Mike M.
Abstract: Measurement of pavement rut is critical to highway agencies for both pavement design and rehabilitation. Historically, rut depth is the only pavement permanent deformation indicator collected with various measurement technologies. Recently, the new draft protocol called AASHTO Standard Practice PP69-10 outlines a set of procedures to derive multiple measures of pavement permanent deformation, including percent deformation, water entrapment depth, rut depth, etc. Multiple parameters can be useful for project-level analysis, but may not be realistic indices for overall permanent deformation evaluation at network level. In this paper, a three-step procedure is applied to evaluate the overall permanent deformation. Transverse profile data are collected on over 200 km (125miles) National Highway Systems using the 1-mm PaveVision3D Ultra data collection system. Twelve attributes for characterising permanent deformation are calculated according to the requirement of PP69-10. Scoring functions of these attributes are elicited using utility theory-based methods with statistics of attributes from the collected sample data-sets. Analytical Hierarchy Process is performed for the development of a comprehensive permanent deformation evaluation system. Additive weights are obtained for all attributes based on pairwise comparisons. A case study is conducted to compare current rut depth-based practice with the proposed new comprehensive evaluation system.